Mitos Permainan Kokkuri San, Ushi No Koku Mairi, Shinrei Shashin, dan Hangonko Dalam Komik Jigoku Sensei Nube Karya Makura Shou Dan Okano Takeshi - Suarji Indrawati, Ni Wayan; Laksmita Sari, Ida Ayu; Damayanti, Silvia (Humanis; Volume 17. No. 1. Oktober 2016, 2016)
The title of thi s research is “ The Myth of Kokkuri san, Ushi no Koku Mairi, Shinrei Shashin and Hangonko Game in Comic entitled Jigoku Sensei Nube by Makura Shou and Okano Takeshi ” . Th is research aims to analyz e the form and the myth of Kokkuri san, ushi no koku mairi, shinrei shashin and hangonko game in a comic entitled Jigoku Sensei Nube by Makura Shou and Okano Takeshi. The theories that are used for analyzing are literary anthropology by Endraswara (2008) and semiotics by Danesi (2010). The results of this research are the games like Kokkuri san, ushi no koku mairi, shinrei shashin and hangonko were adapted from another countries and need equipment to play the games. From the myth, that four games have connection with supernatural creatures and have negative effects if someone play them.